2011
DOI: 10.1088/0004-637x/736/1/18
|View full text |Cite
|
Sign up to set email alerts
|

NARROWBAND IMAGING OF ESCAPING LYMAN-CONTINUUM EMISSION IN THE SSA22 FIELD,

Abstract: We present the results of an ultradeep, narrowband imaging survey for Lyman-continuum (LyC) emission at z ∼ 3 in the SSA22a field. We employ a custom narrowband filter centered at λ = 3640 Å (NB3640), which probes the LyC region for galaxies at z 3.06. We also analyze new and archival NB4980 imaging tuned to the wavelength of the Lyα emission line at z = 3.09, and archival broadband B, V, and R images of the non-ionizing UV continuum. Our NB3640 images contain 26 z 3.06 Lyman break galaxies (LBGs) as well as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
242
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(267 citation statements)
references
References 68 publications
(183 reference statements)
25
242
0
Order By: Relevance
“…The vast majority of known high-redshift galaxies are also opaque to their own ionising radiation, as demonstrated by the success of the well-known Lyman-break selection (as emphasised recently in Cooke et al 2014). Only a few tens of objects are detected in the LyC (Iwata et al 2009;Nestor et al 2011Nestor et al , 2013Mostardi et al 2013). A LyC-leaking galaxy has then peculiar rare properties that we describe below.…”
Section: Ionising Continuum Leakage From Galaxiesmentioning
confidence: 79%
“…The vast majority of known high-redshift galaxies are also opaque to their own ionising radiation, as demonstrated by the success of the well-known Lyman-break selection (as emphasised recently in Cooke et al 2014). Only a few tens of objects are detected in the LyC (Iwata et al 2009;Nestor et al 2011Nestor et al , 2013Mostardi et al 2013). A LyC-leaking galaxy has then peculiar rare properties that we describe below.…”
Section: Ionising Continuum Leakage From Galaxiesmentioning
confidence: 79%
“…In previous articles where z ∼ 3 galaxies were imaged in the LyC, it was shown that emitted ionizing photons can be found at some distance from the center of the galaxies (Iwata et al 2009;Nestor et al 2011). While there is no possible way of acquiring LyC images of Haro 11, we do know that this local galaxy has star-forming regions out to, and beyond, the 30 × 30 LWRS aperture of FUSE.…”
Section: Discussionmentioning
confidence: 99%
“…Iwata et al (2009) and Nestor et al (2011) demonstrated that LyC leakage can be found spatially off-set from the main body of the non-ionizing UV continuum (although some of these detections statistically are likely to be lower redshift contaminants). To estimate the distance from the center at which we would expect most of the ionizing radiation to slip through a picket fence structure in Haro 11, we adopt a simple model with two components -the ionizing stars and the neutral gas.…”
Section: Haro 11mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the recent estimates of f esc for L ≥ L * LBGs at 0 ≤ z ≤ 3 are ≤10% (Bridge et al 2010;Cowie et al 2010;Siana et al 2010;Vanzella et al 2010;Boutsia et al 2011): thus, assuming that the Universe is only re-ionized at z ∼ 7 by stars in galaxies, this implies a fast increase of the galaxy escape fraction going to faint luminosities or to high redshifts (but see Nestor et al 2011 for a larger estimate of the escape fraction of L * LBGs at z ∼ 3).…”
Section: The Impact On the Reionization Processmentioning
confidence: 99%